Friction and wear of liner and grinding ball in iron ore ball mill. (November 2017) - Peng, Yu-xing; Ni, Xu; Zhu, Zhen-cai; Yu, Zhang-fa; Yin, Zi-xin; Li, Tong-qing; Liu, Song-yong; Zhao, La-la; Xu, Jie
Abstract: To understand the friction and wear of working mediums in iron ore ball mills, experiments were conducted using the ball cratering method under dry and wet milling conditions, which mimic the operating conditions in ball mills. The liner sample is made of Mn16 steel, the ball had a diameter of 25 mm and was made of GCr15 steel, and the iron ore powder was screened from the magnetite particles with mesh number of 20. The results indicate that a different wear condition makes the COF change in a converse way and causes a different wear pattern in wear craters, followed by the corresponding temperature rise. Highlights: The effect of ore powder and slurry on friction behavior was discussed through contrast. The friction heating-up was detected by thermal infrared imager. Wear behavior under increasing contact load was analyzed. The wear mechanism under different wear environments was investigated by industrial microscope.